Kurikulum Pendidikan dalam Persepsi Islam - Rahman, Sawaludin; Aly, H. Hery Noer (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
ABSTRACT This study aims to find out how the educational curriculum is in the perception of Islam. This research is a literature study, to seek and find answers through literature review from various relevant sources such as books, journals and direct observations of researchers. The results of the study can be emphasized by the authors in the form of curriculum which is one of the most decisive components in an education system, because of that curriculum is a tool to achieve educational goals and at the same time as a guide in the implementation of teaching at all types and levels of education. Curriculum as an educational design, has a central position, determines the activities and results of education. Its preparation requires a strong foundation, based on the results of in-depth thought and research. In conclusion, in Islamic perception the curriculum component in education is very meaningful because it is an operationalization of the goals aspired to, that goals will not be achieved without the involvement of the educational curriculum. Keywords: Curriculum, Education, Perceptions of Islam